Effects of soybean cultivation on the bacterial population dynamics in cerrado soils - Pereira, João Carlos (2000)
The effect of soybean cultivation on the population dynamics of the bacterial community was evaluated in two "Cerrado" soils of São Paulo State, Brazil. The experimental areas, in the vicinities of the cities of São Carlos and Barretos, were previously cultivated, respectively, with Paspalum notatum and Brachiaria decumbens. The bacterial population densities in these soils varied from 398.1 x 103 to 467.7 x 103 cfu (colony forming units) and from 123 x 103 to 218.8 x 103 cfu/g of dried soil, respectively, in São Carlos and Barretos soils. Soybean cultivation in both soils resulted in increments in the total bacterial population density, in the actinomycetes population, and in the bacterial population resistant to the antibiotics streptomycin and chloramphenicol. Actinomycetes were present in these soils mainly as spores. Soybean cultivation did not alter the actinomycetes spores/hyphae ratio when comparing rhizospheric and non-rhizospheric soils. The results show that soybean cultivation affected the bacterial population of these soils.